NOTES ON TWO LEGUMINOUS GENERA FROM EASTERN INDONESIA - KOSTERMANS, A. J. G. H. (Research Center for Biology, 1952)
Â 1. A new monotypic genus, Kalappia Kostermans, is established for a tree of commercial importance from Celebes, K. celebica Kostermans. The genus is assigned to Caesalpiniaceae (Tribus Cassiae).2. The Papilionaceous genus Desmofischera Holth.(only species: D.monosperma Holth.) is reduced to a synonym of Monarthrocarpus Merr.[only species: M. securiformis (Benth.) Merr.]. Additional collections, from Morotai, are cited.